Pengaruh Model Pembelajaran Explicit Instruction Berbantu Media Audio Visual Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Fiqih di MTs Islamiyah Suluh Medan - Hayatul Fadli; Hasrian Rudi Setiawan (Yayasan Rahmat Islamiyah, 2021)
This study aims to determine the effect of explicit instruction learning model assisted by audio-visual media on student learning outcomes in fiqh subjects. This research method is quantitative research with the type of Quasi Experiment where students are divided into 2 groups, namely the experimental group and the control group. The experimental group was taught using the explicit instruction learning model assisted by audio-visual media while the control group was not. The samples of this study were 26 students of class IX1 for the experimental class and 24 students of class IX2 for the control class. The sampling technique was purposive sampling, the instrument used in the study was a test in the form of multiple collection options that had been tested for validity and reliability. The results obtained were an increase in student learning outcomes when the explicit instruction learning model was applied with the help of audio-visual media on fiqh subjects at MTs Islamiyyah Suluh Medan. This can be seen from the distribution table of the t-table value with the level of freedom (df) is 48 at the 5% significant level is 1.67, while the t-count value is 7.1. The results of the calculation show that the tcount is higher than ttable ((tcount> ttable): 7.1> 1.67). So it can be concluded that Ha is accepted while Ho is rejected, with the hypothesis of